Effects of Supplementing Rumen-Protected Glutathione on Lactation Performance, Nutrients, Oxidative Stress, Inflammation, and Health in Dairy Cows During the Transition Period - Yu Hao; Xuejie Jiang; Rui Sun; Yunlong Bai; Chuang Xu; Yuxi Song; Cheng Xia (Veterinary Sciences)
Glutathione (GSH), widely present in plant and animal cells and crucial for combating oxidative stress and inflammation, has not been evaluated in dairy cows. This study aims to evaluate the effects of rumen-protected glutathione (RPGSH) supplementation on lactation, nutrient metabolism, oxidative stress, inflammation, and health in transition dairy cows. Forty Holstein dairy cows (2.65 ± 0.78 of parity, 2.81 ± 0.24 of body condition score, 9207.56 ± 1139.18 kg of previous 305-day milk yield, 657.53 ± 55.52 kg of body weight, mean ± SD) were selected from a large cohort of 3215 cows on day 21 before expected calving (day −21 ± 3 d). Cows were randomly stratified into four dietary treatment groups (n = 10 per group): control (basal diet + 0 g/d RPGSH); T1 (basal diet + 1.5 g/d RPGSH); T2 (basal diet + 2 g/d RPGSH); and T3 (basal diet + 3 g/d RPGSH). Supplementation commenced approximately 21 days (±3) prepartum and continued through 21 days postpartum. Blood samples were collected at −21 ± 3, −14 ± 3, −7 ± 3, 0, 7, 14, and 21 d for analysis of serum metabolic parameters related to oxidative stress and inflammation. Milk composition was analyzed from samples collected on days 3, 7, 14, and 21 postpartum. Compared with the control group, supplementation with 2 g/d of RPGSH reduced somatic cell count (p < 0.05) and the incidence of postpartum diseases in dairy cows. No differences were observed among the groups in milk yield, milk fat, protein, lactose, total solids, dry matter intake, or energy-corrected milk. However, fat-corrected milk and feed efficiency were higher in the T2 group compared to the control (p < 0.05). Calcium and phosphorus levels did not differ among the groups. Compared to the control group, cows supplemented with 2 g/d RPGSH had lower β-hydroxybutyrate levels and higher glucose levels on days 14 and 21 postpartum (p < 0.05). From days 14 to 21 postpartum, RPGSH supplementation increased blood GSH, serum catalase, and total antioxidant capacity while reducing malondialdehyde, reactive oxygen species, haptoglobin, cortisol, C-reactive protein, and interleukin−6 levels compared with the control group (p < 0.05). The supplementation of 2 g/d RPGSH showed relatively better effects. RPGSH supplementation at 2 g/d improved lactation performance, nutrient metabolism, oxidative stress, and inflammation status in dairy cows, playing a crucial role in maintaining their health. To our knowledge, this is the first report on the effects of supplementing RPGSH additive in Holstein cows.